Acrylate-butadiene block polymer, preparation method and application thereof, composition and application thereof, and polymer coating
By developing acrylate-butadiene block polymers, the content and structure of butadiene segments and acrylate segments are optimized using anionic polymerization process, the problems of high thermal expansion coefficient and poor metal adhesion of liquid butadiene polymers are solved, and the effect of improving thermal expansion properties and enhancing metal adhesion is achieved.
Patent Information
- Application Number
- CN202311428428.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing liquid butadiene polymers have a high thermal expansion coefficient and poor adhesion and adhesion to metals, making it difficult to meet the performance requirements of 5G communication high-frequency copper clad plates.
An acrylate-butadiene block polymer was developed to control the content and structure of the butadiene segments through anionic polymerization process, and combined with the acrylate segments, forming a coating that improves thermal expansion properties and enhances metal adhesion.
It significantly improves the thermal expansion performance of liquid butadiene polymer and its adhesion and adhesion to metals, reduces dielectric loss, and meets the performance requirements of 5G communication high-frequency copper clad plates.
Smart Images

Figure BDA0004525443040000041 
Figure BDA0004525443040000111 
Figure BDA0004525443040000112
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymers, and in particular to an acrylate-butadiene block polymer and a preparation method and application thereof, an acrylate-butadiene block polymer composition and application thereof, and a polymer coating. Background Art
[0002] Liquid butadiene polymer molecular chains contain only carbon-hydrogen structures, have extremely low dielectric constants and dielectric losses, and are the most ideal cross-linking and curing materials for high-frequency copper-clad laminates for 5G communications. According to microstructural classification, liquid butadiene polymers can be divided into 1,4-addition (cis and trans isomers) and 1,2-addition products. Among 1,2-addition products, they can be divided into low-vinyl liquid polybutadiene, medium-vinyl liquid butadiene, and high-vinyl liquid butadiene according to the different contents of 1,2-structures. Common high-cis liquid butadiene polymers and low-cis liquid butadiene polymers have high photo (or thermal) cross-linking reaction activity and poor mechanical properties after curing because most of the double bonds are located in the main chain.
[0003] High vinyl liquid butadiene refers to a liquid butadiene polymer with a 1,2-structure content greater than 65%. Since most of the double bonds are located in the side chains of the molecules, the photo (or thermal) cross-linking reaction activity is high and the photo (or thermal) curing is convenient. However, the heat resistance of the coating formed after curing and the adhesion to the metal surface are not satisfactory.
[0004] CN113698520A discloses a liquid butadiene polymer with a number average molecular weight of 2500-5500, a molecular weight distribution of 1-1.2, and a vinyl content of 85-95%, and the liquid butadiene polymer has a lower dielectric constant and dielectric loss and good film-forming properties, but the heat resistance and adhesion to metal are not satisfactory. CN114106228A discloses a method for preparing a liquid butadiene polymer and its products, which can meet the cross-linking and curing activity requirements of the high-end electronics industry, but also cannot solve the problems of heat resistance and adhesion and adhesion to metal. Therefore, it is of great significance to improve the heat resistance of liquid butadiene polymers, solve the adhesion and adhesion of liquid butadiene polymers to metals, and meet the performance requirements of 5G communication high-frequency copper clad laminates. Summary of the invention
[0005] The present invention aims at the technical problems that the liquid butadiene polymer prepared by the prior art has a high thermal expansion coefficient and unsatisfactory adhesion and bonding to metal. The inventors of the present invention have conducted in-depth research on the anionic polymerization process of the liquid butadiene polymer and developed an acrylate-butadiene block polymer. The coating formed by the acrylate-butadiene block polymer shows improved thermal expansion performance, while improving the adhesion and bonding to metal of the liquid butadiene polymer and reducing dielectric loss, thereby completing the present invention.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an acrylate-butadiene block polymer, wherein, based on the total weight of the acrylate-butadiene block polymer, the content of the butadiene segment is 90-97% by weight, and the content of the acrylate segment is 3-10% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight; the molecular weight of the acrylate-butadiene block polymer measured by GPC presents a unimodal distribution, and the molecular weight distribution is <1.3.
[0007] A second aspect of the present invention provides a method for preparing an acrylate-butadiene block polymer, wherein the method comprises:
[0008] (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring;
[0009] (2) After the product obtained in step (1) is brought into first contact with an alkyl metal compound, diphenylethylene is added, and after a second contact, an acrylate monomer is added for copolymerization to obtain an acrylate-butadiene block polymer; wherein the amount of the acrylate monomer added is 3-10% by weight based on the total weight of the 1,3-butadiene monomer and the acrylate monomer.
[0010] The third aspect of the present invention provides an acrylate-butadiene block polymer prepared by the above method.
[0011] A fourth aspect of the present invention provides a composition comprising the above-mentioned acrylate-butadiene block polymer and at least one additive.
[0012] A fifth aspect of the present invention provides a polymer coating, which contains the above-mentioned acrylate-butadiene block polymer or the above-mentioned composition.
[0013] A sixth aspect of the present invention provides a use of the above-mentioned acrylate-butadiene block polymer or the above-mentioned composition as a crosslinking agent, an adhesive or an electrical insulating material.
[0014] Through the above technical scheme, the acrylate-butadiene block polymer provided by the present invention has good performance. The coating formed by the polymer not only has high peel strength and improved thermal expansion performance for the metal substrate, but also has strong interlayer bonding force of the metal substrate after coating and low dielectric loss, and has broad application prospects in the field of communication technology. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] In the present invention, the term "liquid butadiene polymer" refers to a butadiene polymer having fluidity at 25°C and 1 standard atmospheric pressure.
[0017] In the present invention, the term "1,2-structural unit" refers to a structural unit formed by 1,3-butadiene in a 1,2-polymerization manner, and the content of 1,2-structural units may also be referred to as vinyl content. In the present invention, the content of 1,2-structural units in the polymer is determined by nuclear magnetic resonance spectroscopy.
[0018] In the present invention, the term "cyclized 1,2-structural unit" refers to the vinyl groups in two adjacent 1,2-structural units bonded to form a five-membered ring, and the specific structure is shown below:
[0019]
[0020] In the present invention, the content of cyclized 1,2-structural units in the polymer is determined by nuclear magnetic resonance spectroscopy.
[0021] In the present invention, the content of the acrylic acid ester structural unit in the polymer is determined by nuclear magnetic resonance spectroscopy.
[0022] In the present invention, the specific test method of nuclear magnetic resonance spectroscopy is: using a Bruker AVANCE400 superconducting nuclear magnetic resonance wave instrument ( 1 H-NMR) test, 1The resonance frequency of H nuclei is 400.13 MHz, the spectrum width is 2747.253 Hz, the pulse width is 5 μs, the data point is 16 K, the sample tube diameter is 5 mm, and the solvent is deuterated chloroform (CDCl 3 ), the sample concentration was 15% (mg / mL), the test temperature was room temperature (25°C), the number of scans was 16 times, and the calibration was based on the chemical shift of tetramethylsilane as 0 ppm.
[0023] In the present invention, molecular weight and molecular weight distribution index (M w / M n ) was determined by gel permeation chromatography. The specific test method was: using HLC-8320 gel permeation chromatograph produced by Tosoh Corporation of Japan, the chromatographic column was TSKgelSuperMultiporeHZ-N, the standard column was TSKgel SuperMultiporeHZ, the solvent was chromatographic pure tetrahydrofuran (THF), and narrow distribution polystyrene was used as the standard sample. The polymer sample was prepared into a tetrahydrofuran solution with a concentration of 1 mg / mL, the injection volume was 10 μL, the flow rate was 0.35 mL / min, and the test temperature was 40°C.
[0024] In the present invention, the content of metal elements in the polymer is determined by plasma method, and the specific test method is: using the Optima 8300 full-spectrum direct-reading ICP spectrometer of PerkinElmer (PE) of the United States, equipped with a medium-step grating, a solid-state detector, a dual-path dual solid-state detector in the ultraviolet light region and the visible light region, and using flat-panel plasma technology; the instrument operating parameters are as follows: high-frequency power 1300W, plasma gas flow 15L / min, atomizing gas flow 0.55L / min, auxiliary gas flow 0.2L / min, peristaltic pump speed 1.50mL / min, integration time 10s, plasma axial observation. The sample preparation method is as follows: accurately weigh 2.000g of the sample in a porcelain crucible, place it in a high-temperature resistance furnace and gradually heat it to 500℃, take it out after complete ashing, add 5mL of 10 volume % dilute nitric acid, slowly heat it on a hot plate until it is completely dissolved, evaporate the solution to dryness, add 1mL of concentrated nitric acid, transfer it to a 50mL volumetric flask, and make up to volume with water, and prepare a reagent blank solution at the same time.
[0025] In the present invention, the linear thermal expansion coefficient is measured by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018.
[0026] In the present invention, the peel strength between the polymer coating and the metal substrate (copper foil) is tested using the method specified in IPC-TM-650.
[0027] In the present invention, the interlayer bonding strength of the metal substrate after the polymer coating is cured is tested according to the DB44T1088-2012 standard.
[0028] The first aspect of the present invention provides an acrylate-butadiene block polymer, wherein, based on the total weight of the acrylate-butadiene block polymer, the content of the butadiene segment is 90-97% by weight, and the content of the acrylate segment is 3-10% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight; the molecular weight of the acrylate-butadiene block polymer measured by GPC presents a unimodal distribution, and the molecular weight distribution is less than 1.3.
[0029] According to the present invention, based on the total weight of the acrylate-butadiene block polymer, the content of the acrylate segment is 3-10% by weight. In the present invention, the inventors have found that when the content of the acrylate segment in the polymer is controlled to meet the above range, the adhesion of the coating formed by the polymer to the metal substrate can be significantly improved, and the dielectric loss of the polymer coating can be reduced. Specifically, when the content of the acrylate segment is less than 3% by weight, the adhesion between the coating formed by the polymer and the metal is not significantly improved; when the content of the acrylate segment is greater than 10% by weight, the dielectric loss of the polymer coating increases. Based on the total weight of the acrylate-butadiene block polymer, the content of the acrylate segment can be 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, preferably 4-9% by weight.
[0030] In the present invention, in the acrylate-butadiene block polymer, the butadiene segment is a high-vinyl cyclized butadiene segment.
[0031] According to the present invention, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of 1,4-structural units is 10-25% by weight, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25% by weight. Preferably, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of 1,4-structural units is 10-20% by weight. When the content of 1,4-structural units is less than 10% by weight, it is necessary to carry out at a lower temperature, which affects the content of cyclized structural units in the polymer; when the content of 1,4-structural units is greater than 25% by weight, the double bonds that can participate in curing and crosslinking are reduced, the crosslinking density of the polymer coating is reduced, and the mechanical properties are deteriorated.
[0032] According to the present invention, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of 1,2-structural units is 50-70% by weight, for example, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70% by weight. Preferably, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of 1,2-structural units is 50-65% by weight. More preferably, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of 1,2-structural units is 52-62% by weight. When the content of 1,2-structural units is less than 50% by weight, the crosslinking density of the coating formed by the polymer decreases and the mechanical properties deteriorate; when the content of 1,2-structural units is greater than 70% by weight, the content of cyclized 1,2-structural units decreases, which is not conducive to improving the thermal expansion coefficient.
[0033] According to the present invention, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of the cyclized 1,2-structural unit is 15-35% by weight, such as 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35% by weight. Preferably, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of the cyclized 1,2-structural unit is 18-35% by weight. More preferably, based on the total weight of the butadiene segments in the acrylate-butadiene block polymer, the content of the cyclized 1,2-structural unit is 20-35% by weight. In the present invention, if the content of cyclized 1,2-structural units is less than 15% by weight, the thermal expansion coefficient of the coating after curing is not significantly improved; if the content of cyclized 1,2-structural units is greater than 35% by weight, in order to prepare liquid polybutadiene rubber with a higher cyclized structure content, increasing the polymerization temperature becomes the only option, which is not conducive to increasing the total 1,2-structure content of the polymer, and the peel strength between the coating formed by the polymer and the metal substrate decreases, and the interlayer bonding force between copper foils decreases after the polymer coating is cured.
[0034] According to the present invention, the weight ratio of the cyclized 1,2-structure 1,2-structure unit to the 1,2-structure unit in the acrylate-butadiene block polymer is 0.2-0.7: 1, preferably 0.3-0.6: 1. In the present invention, when the molar ratio of the cyclized 1,2-structure unit to the 1,2-structure unit in the liquid butadiene polymer meets the above range, the comprehensive performance of the polymer coating after curing is better.
[0035] In the present invention, the inventors have found that when the molecular weight of the acrylate-butadiene block polymer measured by GPC presents a unimodal distribution, it indicates that the carbon-carbon double bond of the acrylate participates in the polymerization reaction, and no side reaction involving the carbon-oxygen double bond occurs. The end of the molecular chain has a certain polarity, which can improve the adhesion between the polymer and the metal. The dynamic viscosity of the polymer remains basically unchanged, thereby ensuring the processing performance of the polymer.
[0036] According to the present invention, the number average molecular weight (M n ) is 3500-10000 g / mol, preferably 4500-8000 g / mol.
[0037] According to the present invention, the acrylate-butadiene block polymer has not only a molecular weight suitable for molding, but also a narrow molecular weight distribution. Preferably, according to the present invention, the molecular weight distribution index (M w / M n ) is 1-1.25, preferably 1-1.2.
[0038] According to the present invention, based on the total weight of the acrylate-butadiene block polymer, the weight content of the metal element in the polymer is 200 ppm or less, preferably 100 ppm or less, more preferably 50 ppm or less, and further preferably 20 ppm or less. Controlling the metal content in the polymer is conducive to reducing the dielectric constant and dielectric loss of the cross-linked and cured product, thereby obtaining better applications in the field of electronic communications.
[0039] According to the present invention, the linear thermal expansion coefficient of the acrylate-butadiene block polymer after curing is 40×10 -6 m / m / ℃-80×10 -6 m / m / ℃, preferably 40×10 -6 m / m / ℃-70×10 -6 m / m / ℃, more preferably 40×10 -6 m / m / ℃-60×10 -6 m / m / ℃.
[0040] According to the present invention, the peel strength between the coating formed by the acrylate-butadiene block polymer and the metal substrate (such as copper foil) is 1-1.3 N / mm, preferably 1.05-1.3 N / mm, and more preferably 1.1-1.3 N / mm;
[0041] According to the present invention, after the coating formed by the acrylate-butadiene block polymer is cured, the interlayer bonding force of the metal substrate is 0.9-1.2 N / mm, preferably 0.95-1.2 N / mm, and more preferably 1-1.2 N / mm.
[0042] According to the present invention, the dielectric loss of the 10 GHz planar capacitor of the metal matrix laminate after curing of the acrylate-butadiene block polymer is ≤0.0042, preferably ≤0.0040, and more preferably ≤0.0038.
[0043] A second aspect of the present invention provides a method for preparing an acrylate-butadiene block polymer, wherein the method comprises:
[0044] (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring;
[0045] (2) After the product obtained in step (1) is brought into first contact with an alkyl metal compound, diphenylethylene is added, and after a second contact, an acrylate monomer is added for copolymerization to obtain an acrylate-butadiene block polymer; wherein the amount of the acrylate monomer added is 3-10% by weight based on the total weight of the 1,3-butadiene monomer and the acrylate monomer.
[0046] In the present invention, the term “continuously” means that the 1,3-butadiene monomer required for polymerization is added gradually and continuously into the reactor, rather than adding all the 1,3-butadiene monomer required for polymerization into the reactor at one time.
[0047] In the present invention, by continuously adding the 1,3-butadiene monomer required for polymerization into the reactor, the polymerization reaction can be precisely controlled, ensuring that the active species of the initiator are always in a hungry state, which is more conducive to the formation of the 1,2-cyclized structure. Further, the content of the cyclized 1,2-structure in the butadiene polymer is increased. After the butadiene polymer with a high content of cyclized 1,2-structure is contacted with an alkyl metal compound, it is copolymerized with an acrylate monomer to obtain the acrylate-butadiene block polymer described in the first aspect of the present invention. In particular, when the addition amount of the acrylate monomer in the 1,3-butadiene monomer and the acrylate monomer meets the above range, the adhesion between the polymer and the metal substrate can be significantly improved, and the thermal expansion coefficient and dielectric loss of the polymer coating after curing can also be controlled within an ideal range.
[0048] In the present invention, diphenylethylene is added before the acrylate monomer, which can reduce the reaction activity and inhibit the occurrence of side reactions, so that the molecular weight of the prepared acrylate-butadiene block polymer measured by GPC presents a unimodal distribution.
[0049] In the present invention, in the acrylate-butadiene block copolymer, the 1,2-structural unit content, the 1,4-structural unit content and the cyclized 1,2-structural unit content in the butadiene segment are determined by step (1), and the copolymerization reaction with the acrylate monomer in step (2) does not affect the 1,2-structural unit content, the 1,4-structural unit content and the cyclized 1,2-structural unit content in the butadiene segment.
[0050] Furthermore, based on the total weight of the 1,3-butadiene monomer and the acrylate monomer, the amount of the acrylate monomer added is 4-9% by weight.
[0051] According to the present invention, the conditions of the copolymerization reaction include: a polymerization temperature of -20°C to 20°C, and a polymerization time of 30-60 minutes.
[0052] Furthermore, the conditions of the copolymerization reaction include: a polymerization temperature of -15°C to 15°C, and a polymerization time of 30-50 minutes.
[0053] According to the present invention, the acrylic acid ester monomer is at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate and methyl-2-hydroxyethyl (meth)acrylate.
[0054] According to the present invention, based on 100 g of solvent, the rate of adding 1,3-butadiene into the reactor is 0.1-0.5 g / min, preferably 0.15-0.35 g / min.
[0055] According to the present invention, butadiene monomer is continuously processed at a temperature of 60°C to 90°C, preferably at a temperature of 70°C to 90°C.
[0056] In the present invention, the anionic solution polymerization reaction can be carried out under a pressure of 0.005-1.5MPa, more preferably under a pressure of 0.1-1MPa, and further preferably under a pressure of 0.2-0.6MPa. In the present invention, pressure refers to gauge pressure. The polymerization time can be selected according to the final monomer concentration and polymerization temperature of the polymerization reaction, and can generally be 30-120min, preferably 40-80min.
[0057] In the present invention, the anionic polymerization reaction is carried out in an atmosphere formed by an inert gas. The inert gas refers to a gas that does not chemically interact with reactants, reaction products and solvents under polymerization conditions, such as nitrogen and / or zero group element gas (such as argon).
[0058] According to the present invention, in step (2), the alkyl metal compound is selected from alkyl aluminum compounds and / or alkyl magnesium compounds.
[0059] According to the present invention, the alkyl metal compound is at least one selected from trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tributylaluminum, triisobutylaluminum, diethylmagnesium, dibutylaluminum and n-butyl-sec-butylmagnesium.
[0060] According to the present invention, the molar ratio of the alkyl metal compound to the initiator is 0.5-3:1.
[0061] In the present invention, when the molar ratio of the alkyl metal compound to the initiator is controlled to meet the above range, the side reaction in the anionic polymerization process of acrylate can be suppressed to prepare a butadiene-acrylate block polymer. Furthermore, the molar ratio of the alkyl metal compound to the initiator is 1-2:1.
[0062] According to the present invention, the time for the first contact between the product obtained in step (1) and the alkyl metal compound is 1-10 minutes.
[0063] In the present invention, the product containing the active chain of butadiene polymer obtained in step (1) is first contacted with an alkyl metal compound in advance, and the time of the first contact is specifically controlled to meet the above range, so that the butadiene active chain and the metal alkyl compound form a complex with a specific structure, thereby ensuring the normal progress of the anionic polymerization of acrylate.
[0064] Furthermore, the first contact time between the product obtained in step (1) and the alkyl metal compound is 2-8 minutes.
[0065] According to the present invention, the second contacting time is 10-20 minutes.
[0066] According to the present invention, the diphenylethylene is selected from 1,1-diphenylethylene and / or 1,2-diphenylethylene, preferably 1,1-diphenylethylene.
[0067] According to the present invention, the molar ratio of the diphenylethylene to the initiator is 1-2:1, preferably 1-1.5:1.
[0068] In a preferred embodiment, the component A is one or more compounds selected from the group consisting of compounds shown in formula I.
[0069]
[0070] In Formula I, R 2 and R 3 The same or different, each independently C 1 -C 6 of alkyl.
[0071] In Formula I, R 1 is a monovalent group represented by formula II,
[0072]
[0073] In Formula II, m is an integer of 1-5, for example, 1, 2, 3, 4 or 5.
[0074] In Formula II, R 4 and R 5 are the same or different, each independently a hydrogen atom or a C 1 -C 6 The alkyl group is preferably a hydrogen atom.
[0075] In Formula II, R 6 For-NR 7 R 8 , or C 3 -C 6 Oxyheterocycloalkyl, R 7 and R 8 The same or different, each independently C 1 -C 6 of alkyl.
[0076] In Formula I and Formula II, C 1 -C 6 The alkyl groups include C 1 -C 6 The straight chain alkyl and C 3 -C 6 The branched alkyl group may include, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl and n-hexyl.
[0077] In a preferred embodiment of the present invention, the component A is N,N,N',N'-tetramethylethylenediamine and / or N,N-dimethyltetrahydrofurfurylamine. In a particularly preferred embodiment, the component A is N,N,N',N'-tetramethylethylenediamine.
[0078] In a preferred embodiment, the component B is one or more compounds selected from the group consisting of compounds shown in formula III.
[0079] R 9 -OM1 (Formula III)
[0080] In Formula III, R 9 C 1 -C 20 Alkyl, C with heteroatom substituent 1 -C 20 Alkyl or C 6 -C 30 The aromatic group,
[0081] M 1 is an alkali metal atom, for example, Li, Na or K, preferably Na.
[0082] In formula III, C 1 -C 20 The alkyl groups include C 1 -C 20 The straight chain alkyl and C 3 -C 20 Specific examples of the branched alkyl group may include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl and its isomers, n-hexyl and its isomers, n-heptyl and its isomers, n-octyl and its isomers, n-nonyl and its isomers, n-decyl and its isomers, undecyl and its isomers, dodecyl and its isomers, tridecyl and its isomers, tetradecyl and its isomers, pentadecyl and its isomers, hexadecyl and its isomers, heptadecyl and its isomers, octadecyl and its isomers, nonadecyl and its isomers, and eicosyl and its isomers.
[0083] In Formula III, C having a heteroatom-containing substituent 1 -C 20 The substituent in the alkyl group is preferably a cycloalkyl group containing a heteroatom, and specific examples of the heteroatom may include, but are not limited to, an oxygen atom, a sulfur atom or a nitrogen atom. In a preferred embodiment, the heteroatom in the substituent containing a heteroatom is an oxygen atom, and the substituent containing a heteroatom is a cycloalkyl group containing an oxygen atom, such as an acrylate substituent, an oxetane substituent, an oxetane substituent, a tetrahydrofuran substituent, or an oxetane substituent.
[0084] In formula III, C 6 -C 30 Specific examples of the aryl group may include, but are not limited to, phenyl, o-tolyl, m-tolyl, p-tolyl, o-ethylphenyl, m-ethylphenyl, p-ethylphenyl, o-tert-butylphenyl, m-tert-butylphenyl, p-tert-butylphenyl, p-dodecylphenyl, 2,4-di-n-butylphenyl, p-n-propylphenyl, and 2,4-diethylphenyl.
[0085] In a preferred embodiment of the present invention, the component B is preferably one or more of sodium tetrahydrofurfuryl alcohol, sodium tert-amyl oxide, sodium tert-butoxylate, sodium n-hexoxide and sodium menthol.
[0086] In a preferred embodiment of the present invention, the molar ratio of component B to component A is 0.1-0.5:1, preferably 0.15-0.45:1, and more preferably 0.2-0.4:1.
[0087] In a preferred embodiment of the present invention, the amount of the structure regulator can be adjusted according to the amount of the monomer (i.e., 1,3-butadiene) and / or the anionic polymerization initiator. Relative to 1 mol of the initiator, the amount of the component A can be 0.5-2 mol, preferably 0.7-1.5 mol. Relative to 1 mol of the initiator, the amount of the component B can be 0.1-0.5 mol, preferably 0.2-0.4 mol.
[0088] In a preferred embodiment of the present invention, the initiator is an organic lithium initiator, preferably an organic monolithium compound, and more preferably a compound represented by formula IV,
[0089] R 10 Li (Formula IV)
[0090] In Formula IV, R 10 C 1 -C 6 Alkyl, C 3 -C 12 Cycloalkyl, C 7 -C 14 Arylalkyl or C 6 -C 12 The aromatic group.
[0091] In Formula IV, C 1 -C 6 The alkyl groups include C 1 -C 6 The straight chain alkyl and C 3 -C 6 The branched alkyl group may include, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl and n-hexyl.
[0092] In Formula IV, C 3 -C 12 Specific examples of the cycloalkyl group may include, but are not limited to, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, 4-ethylcyclohexyl, 4-n-propylcyclohexyl, and 4-n-butylcyclohexyl.
[0093] In Formula IV, C 7-C 14 Specific examples of the aralkyl group may include, but are not limited to, phenylmethyl, phenylethyl, phenyl-n-propyl, phenyl-n-butyl, phenyl-t-butyl, phenyl-isopropyl, phenyl-n-pentyl, and phenyl-n-butyl.
[0094] In Formula IV, C 6 -C 12 Specific examples of the aryl group may include, but are not limited to, phenyl, naphthyl, 4-methylphenyl, and 4-ethylphenyl.
[0095] In a preferred embodiment of the present invention, specific examples of the initiator may include, but are not limited to: one or more of ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, phenyl lithium, 2-naphthyl lithium, 4-butylphenyl lithium, 4-tolyl lithium, cyclohexyl lithium and 4-butylcyclohexyl lithium. Preferably, the initiator is n-butyl lithium and / or sec-butyl lithium, and more preferably, the initiator is n-butyl lithium.
[0096] In the present invention, the amount of the anionic polymerization initiator can be selected according to the expected number average molecular weight of the acrylate-butadiene block polymer. Preferably, the amount of the anionic polymerization initiator is such that the number average molecular weight of the prepared liquid butadiene polymer is 3500-10000 g / mol, preferably 4500-8000 g / mol. The method for determining the specific amount of the anionic polymerization initiator according to the expected polymer molecular weight is well known to those skilled in the art and will not be described in detail herein.
[0097] According to the present invention, the solvent is a solvent containing an aliphatic heterocycle. The term "aliphatic heterocycle" refers to a cycloalkane in which at least one carbon atom on the ring is replaced by a heteroatom. The heteroatom in the aliphatic heterocycle can be an oxygen atom, a nitrogen atom or a sulfur atom, preferably an oxygen atom. The solvent can be one or more selected from tetrahydrofuran, cyclopentane oxide, cyclohexane oxide and 1,4-dioxane. The solvent can be used alone or in combination. In a preferred embodiment, the solvent is an aliphatic heterocycle solvent, more preferably an oxacycloalkane. In a particularly preferred embodiment, the solvent is tetrahydrofuran.
[0098] In the present invention, the content of 1,3-butadiene monomer can be 1-40% by weight, preferably 10-30% by weight, based on the total weight of the solvent and the 1,3-butadiene monomer. In the present invention, the content of 1,3-butadiene monomer refers to the total weight percentage of 1,3-butadiene monomer determined based on the total weight of the solvent and the 1,3-butadiene monomer after the polymerization reaction.
[0099] In the present invention, the preparation method further comprises: after the copolymerization reaction is completed, adding a terminator, removing the organic lithium initiator and the solvent, and obtaining the acrylate-butadiene block polymer.
[0100] In the present invention, there is no particular limitation on the type and amount of the terminator, and conventional terminators in the art may be used and added in conventional amounts in the art.
[0101] In the present invention, the preparation method may further include: removing at least part of the metal ions in the polymerization reaction mixture to obtain a purified polymerization reaction mixture. The polymerization reaction mixture may be washed to remove at least part of the metal ions.
[0102] In a preferred embodiment, the method for removing at least part of the metal ions in the polymerization mixture comprises: mixing the polymerization mixture with a washing liquid, and separating the oil phase from the mixture, wherein the washing liquid is water or an aqueous solution containing an acid. In this preferred embodiment, the acid is preferably an inorganic acid, more preferably one or more of sulfuric acid, nitric acid, hydrochloric acid and carbonic acid. When the acid is carbonic acid, carbonic acid can be formed by passing carbon dioxide gas into the mixture of the polymerization mixture and water and / or adding dry ice to the polymerization mixture.
[0103] In a more preferred example of this preferred embodiment, the washing liquid includes a first washing liquid and a second washing liquid, the first washing liquid is an aqueous solution containing acid I, the second aqueous solution is an aqueous solution containing acid II, the acid I is one or more of sulfuric acid, hydrochloric acid and nitric acid, and the acid II is carbonic acid, and the method for removing at least part of the metal ions in the polymerization reaction mixture comprises: mixing the polymerization reaction mixture with the first washing liquid to obtain a first mixture, separating a first oil phase from the first mixture, removing at least part of the solvent in the first oil phase, and obtaining a crude product of liquid butadiene polymer; in the presence of carbon dioxide, mixing the first oil phase with water to obtain a second mixture, separating a second oil phase from the second mixture, removing at least part of the volatile components in the second oil phase, and obtaining a liquid butadiene polymer. In this more preferred example, the weight ratio of the first washing liquid to the monomer is preferably 1-5:1, more preferably 2-4:1, the molar ratio of the acid I in the first washing liquid to the anionic polymerization initiator is preferably 0.5-3:1, more preferably 0.8-2:1, and the acid I is in the form of H + The weight ratio of the second washing liquid to the monomer is 1-2: 1, the molar ratio of the acid II in the second washing liquid to the anionic polymerization initiator is preferably 0.1-1: 1, the acid II to H + count.
[0104] In the present invention, various reagents used in the preparation method are preferably refined by conventional methods in the art before use to remove impurities (especially water) therein. The method for refining the reagents is well known in the art and will not be described in detail herein.
[0105] In the present invention, the anionic solution polymerization reaction can be carried out by batch polymerization or continuous polymerization, without particular limitation.
[0106] The third aspect of the present invention provides an acrylate-butadiene block polymer prepared by the above method.
[0107] The butadiene segments in the acrylate-butadiene block polymer prepared by the method described in the second aspect of the present invention not only have a high 1,2-structural unit content, but also part of the 1,2-structural units form a ring structure and contain acrylate segments. The coating formed by using the raw material containing the acrylate-butadiene block polymer prepared by the method described in the second aspect of the present invention shows more excellent thermal expansion performance while maintaining high peel strength and interlayer bonding strength.
[0108] A fourth aspect of the present invention provides a composition comprising the above-mentioned acrylate-butadiene block polymer and at least one additive.
[0109] In the present invention, the additive can be a substance that can give the composition new properties and / or improve the existing properties of the composition. As a preferred example, the additive contains an antioxidant. The antioxidant can be a conventional selection, for example, the antioxidant can be a phenolic and / or amine antioxidant. Specifically, the antioxidant can be one or more of 4,6-dioctylthiomethyl o-cresol, tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester (i.e., antioxidant 264), tris(2,4-di-tert-butylphenyl) phosphite (i.e., antioxidant 168), 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid octadecyl ester (i.e., antioxidant 1076), 2,6-di-tert-butyl-p-cresol, tert-butylcatechol and 2,2'-methylene-bis(4-methyl-6-tert-butylphenol). The content of the antioxidant may be 0.005-2 parts by weight, preferably 0.01-1 parts by weight, relative to 100 parts by weight of the acrylate-butadiene block polymer.
[0110] A fifth aspect of the present invention provides a polymer coating, which contains the above-mentioned acrylate-butadiene block polymer or the above-mentioned composition.
[0111] In the present invention, the polymer coating not only has high adhesion and bonding to the substrate, but also has a reduced thermal expansion coefficient, showing improved thermal expansion performance.
[0112] A sixth aspect of the present invention provides a use of the above-mentioned acrylate-butadiene block polymer or the above-mentioned composition as a crosslinking agent, an adhesive or an electrical insulating material.
[0113] The present invention will be described in detail below with reference to the embodiments, but the scope of the present invention is not limited thereby.
[0114] Unless otherwise specified, normal temperature and room temperature both refer to 25±3℃.
[0115] In the following examples and comparative examples, the microstructure of the polymer was measured using a Bruker AVANCE400 superconducting nuclear magnetic resonance instrument ( 1 H-NMR) determination, 1 The resonance frequency of H nuclei is 400.13 MHz, the spectrum width is 2747.253 Hz, the pulse width is 5 μs, the data point is 16 K, the sample tube diameter is 5 mm, and the solvent is deuterated chloroform (CDCl 3 ), the sample concentration was 15% (W / V), the test temperature was room temperature, the number of scans was 16 times, and the calibration was based on the chemical shift of tetramethylsilane as 0 ppm.
[0116] In the following examples and comparative examples, the number average molecular weight and molecular weight distribution index of the polymers were determined by gel permeation chromatography analysis. The gel permeation chromatography analysis was performed using an HLC-8320 gel permeation chromatograph produced by Tosoh Corporation of Japan. The chromatographic column was TSKgel SuperMultiporeHZ-N, the standard column was TSKgel SuperMultiporeHZ, the solvent was chromatographically pure tetrahydrofuran (THF), and narrow distribution polystyrene was used as the standard sample. The polymer sample was prepared into a tetrahydrofuran solution with a mass concentration of 1 mg / mL, the injection volume was 10.00 μL, the flow rate was 0.35 mL / min, and the test temperature was 40°C.
[0117] In the following examples and comparative examples, the content of metal elements in the polymer was determined by a plasma method.
[0118] In the following examples and comparative examples, the linear thermal expansion coefficient is measured by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018.
[0119] In the following examples and comparative examples, the peel strength between the polymer coating and the copper foil was tested using the method specified in IPC-TM-650 2.4.08C.
[0120] In the following examples and comparative examples, the interlayer bonding strength of the copper foil is tested according to the DB44T1088-2012 standard.
[0121] In the following examples and comparative examples, the dielectric loss of the copper foil laminated 10 GHz planar capacitor was tested using the IPC-TM-650-2.5.5.13 method.
[0122] In the following examples and comparative examples, the following chemical reagents are involved:
[0123] Antioxidant 264, antioxidant 168 and antioxidant 1076 were purchased from Sinopharm Reagent Company.
[0124] Tetrahydrofuran: chromatographically pure, soaked on molecular weight sieves for 15 days, water content less than 5ppm (weight content).
[0125] 1,3-Butadiene: polymerization grade, purchased from Yanshan Petrochemical.
[0126] n-Butyl lithium: purchased from J&K Reagent Company, as a 1.6 mol / L hexane solution.
[0127] 2,2-Di(2-tetrahydrofuryl)propane) (DTHFP): purchased from J&K Reagent Co., analytical grade.
[0128] N,N,N',N'-Tetramethylethylenediamine (TMEDA): purchased from J&K Reagent Co., analytical grade.
[0129] Sodium tert-amyloxide (STA): purchased from J&K Reagent Company, 1.4 mol / L tetrahydrofuran solution.
[0130] Sodium tetrahydrofurfuryl alcohol (THFOA): purchased from Inotech Reagent Company, 1 mol / L tetrahydrofuran solution.
[0131] Sodium menthol (SMT): purchased from Inotech Reagent Company, 1 mol / L tetrahydrofuran solution.
[0132] 1,1-Diphenylethylene (DPE): purchased from Qingkai Huafeng Reagent Company, purity >99%.
[0133] Methyl methacrylate (MMA): purchased from Qingkai Huafeng Reagent Company, purity>99%.
[0134] Ethyl methacrylate (EMA): purchased from Qingkai Huafeng Reagent Company, purity> 99%.
[0135] Triisobutylaluminum (Al): purchased from Inotech Reagent Company, 1.0 mol / L hexane solution.
[0136] n-Butylmagnesium (Mg): purchased from Inotech Reagent Company, 1.0 mol / L hexane solution.
[0137] Sulfuric acid: purchased from J&K Reagent Company, concentration is 98 wt%, prepared with water to make a 20 wt% solution.
[0138] Nitric acid: purchased from Sinopharm Reagent Company, with a concentration of 68% by weight, prepared with water to a 20% by weight solution.
[0139] Example 1
[0140] This example is used to illustrate the acrylate-butadiene block polymer and the preparation method thereof of the present invention.
[0141] (1) Under nitrogen protection, tetrahydrofuran (THF), structure regulator 1, structure regulator 2, and n-butyl lithium (types and amounts are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) are added to a 5 L reactor, the temperature in the reactor is controlled to be the polymerization reaction temperature listed in Table 1, and 1,3-butadiene monomer is continuously added to the reactor (the addition rate and time are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds); and anionic solution polymerization is carried out at the temperature and pressure listed in Table 1 to obtain a polymerization reaction mixture containing a high vinyl cyclized liquid butadiene polymer.
[0142] (2) Adding a designed amount of an alkyl aluminum (magnesium) compound (the type and amount are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) to the high vinyl cyclized liquid butadiene polymer reaction mixture obtained in step (1), adding a designed amount of DPE after mixing for 5 minutes, and adding a designed amount of an acrylate monomer (the type and amount are shown in Table 1, and the amounts listed in Table 1 are all measured based on pure compounds) after 15 minutes, and conducting an anionic solution polymerization reaction at the temperature and pressure listed in Table 1 to obtain a reaction solution containing an acrylate-butadiene block polymer.
[0143] (3) Add water and acid (the specific amounts and types of acids are listed in Table 2, and the amounts listed in Table 2 are all measured based on pure compounds) to the polymerization reaction mixture obtained in step (2), stir for 15 minutes, and then stand for stratification to separate the aqueous phase. The obtained oil phase is subjected to reduced pressure distillation to obtain a crude acrylate-butadiene block polymer.
[0144] (4) adding water to the crude acrylate-butadiene block polymer obtained in step (3), introducing carbon dioxide gas with stirring (the specific amounts of water and carbon dioxide are listed in Table 2), then standing to separate the layers, separating the aqueous phase, subjecting the obtained oil phase to reduced pressure distillation, and adding an antioxidant to the distillation residue (the specific amount and type are listed in Table 2) to obtain a composition LPB1 containing acrylate-butadiene block polymer, wherein the structural property parameters of the acrylate-butadiene block polymer are listed in Table 3.
[0145] Embodiment 2-10
[0146] Examples 2-10 are used to illustrate the acrylate-butadiene block polymer and the preparation method thereof of the present invention.
[0147] Examples 2-10 use the same method as Example 1 to prepare acrylate-butadiene block polymers, except that step (1) and step (2) are reacted under the conditions shown in Table 1, and step (3) and step (4) are used to treat the reaction mixture containing acrylate-butadiene block polymer obtained in step (1) under the conditions shown in Table 2, thereby respectively obtaining acrylate-butadiene block polymer compositions LPB2-LPB10, wherein the structural property parameters of the acrylate-butadiene block polymers are listed in Table 3.
[0148] Comparative Example 1
[0149] The same method as in Example 1 was used to prepare an acrylate-butadiene block polymer, except that no alkyl aluminum was added in step (2). The acrylate-butadiene block polymer composition DLPB1 was obtained, and the molecular weight distribution of the polymer was significantly broadened. The structural property parameters are listed in Table 3.
[0150] Comparative Example 2
[0151] The liquid butadiene polymer was prepared in the same manner as in Example 1, except that alkyl aluminum, DPE and acrylate were not added, to obtain a composition DLPB2 containing a liquid butadiene polymer, wherein the structural property parameters of the liquid butadiene polymer are listed in Table 3.
[0152] Comparative Example 3
[0153] The acrylate-butadiene block polymer was prepared by the same method as in Example 1, except that 5 g of methyl methacrylate was added in step (2) to obtain an acrylate-butadiene block polymer composition DLPB3. The structural property parameters of the acrylate-butadiene block polymer in the composition are listed in Table 3.
[0154] Comparative Example 4
[0155] The acrylate-butadiene block polymer was prepared by the same method as in Example 1, except that 80 g of methyl methacrylate was added to obtain an acrylate-butadiene block polymer composition DLPB4. The structural property parameters of the acrylate-butadiene block polymer in the composition are listed in Table 3.
[0156] Comparative Example 5
[0157] The acrylate-butadiene block polymer was prepared by the same method as in Example 1, except that DPE was not added in step (2), to obtain an acrylate-butadiene block polymer composition DLPB5, wherein the molecular weight of the acrylate-butadiene block polymer in the composition showed a bimodal distribution, and its structural property parameters are listed in Table 3.
[0158] Table 1
[0159]
[0160]
[0161] a Based on 100g solvent
[0162] Table 1
[0163]
[0164] a Based on 100g solvent
[0165] Table 2
[0166]
[0167]
[0168] b Relative to 100g of acrylate-butadiene block polymer
[0169] Table 3
[0170]
[0171] Note: MA represents the acrylate segment, PB represents the butadiene segment, Mn represents the number average molecular weight of the acrylate-butadiene block polymer, Mw / Mn represents the molecular weight distribution index of the acrylate-butadiene block polymer, 1,2-PB represents the content of 1,2-structural units in the butadiene segment, C-1,2-PB represents the content of cyclized 1,2-structural units in the butadiene segment, and 1,4-PB represents the content of 1,4-structural units in the liquid butadiene polymer.
[0172] It can be seen from Table 3 that the acrylate-butadiene block polymer provided by the present invention comprises a butadiene segment and an acrylate segment, and the acrylate segment has a specific content. At the same time, the butadiene segment has a higher 1,2-structural unit content and a cyclized 1,2-structural unit content. The acrylate-butadiene block polymer has a narrow molecular weight distribution and is an ideal adhesive for the high-frequency communication field.
[0173] Test Case
[0174] Compositions LPB1 to LPB10 (wherein the acrylamide-butadiene polymer is 100 g and the antioxidant is 0.16 g) prepared in Examples 1-10 were uniformly coated on the surface of the copper foil with a coating thickness of 0.8 mm. The coating was cross-linked and cured at 120° C. for 2 hours. The peel strength was measured by the method specified in IPC-TM-650 2.4.08C. The interlayer bonding force between the copper foils was tested according to the method specified in DB44T1088-2012. The linear thermal expansion coefficient was measured by thermomechanical analysis (TMA) according to the method specified in GB / T 36800.2-2018. The experimental results are listed in Table 4.
[0175] Test comparison
[0176] The peel strength, interlayer bonding force, thermal expansion coefficient and dielectric loss of the compositions DLPB1 to DLPB5 prepared in Comparative Examples 1-5 were measured using the same method as in the test example. The experimental results are listed in Table 4.
[0177] Table 4
[0178]
[0179] It can be seen from the results in Table 4 that the polymer coating formed by the acrylate-butadiene block polymer provided by the present invention has a low thermal expansion coefficient after curing, high peel strength with the copper foil, good interlayer bonding strength between the copper foils, and low dielectric loss of the copper foil laminate.
[0180] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An acrylate-butadiene block polymer, characterized in that: Based on the total weight of the acrylate-butadiene block polymer, the content of the butadiene segment is 90-97% by weight, and the content of the acrylate segment is 3-10% by weight; based on the total weight of the butadiene segment, the content of the 1,4-structural unit is 10-25% by weight, the content of the 1,2-structural unit is 50-70% by weight, and the content of the cyclized 1,2-structural unit is 15-35% by weight. The molecular weight of the acrylate-butadiene block polymer measured by GPC presents a unimodal distribution, and the molecular weight distribution is less than 1.
3.
2. The acrylate-butadiene block polymer according to claim 1, wherein Based on the total weight of the acrylate-butadiene block polymer, the content of the butadiene segment is 92-96% by weight, and the content of the acrylate segment is 4-9% by weight; Preferably, based on the total weight of the butadiene segment, the content of 1,4-structural units is 10-20 wt %; the content of 1,2-structural units is 50-65 wt %, preferably 52-62 wt %; the content of cyclized 1,2-structural units is 18-35 wt %, preferably 20-35 wt %; Preferably, the weight ratio of the cyclized 1,2-structural unit to the 1,2-structural unit in the acrylate-butadiene block polymer is 0.2-0.7:1, preferably 0.3-0.6:
1.
3. The acrylate-butadiene block polymer according to claim 1 or 2, wherein The number average molecular weight of the acrylate-butadiene block polymer is 3500-10000 g / mol, preferably 4500-8000 g / mol; Preferably, the molecular weight distribution index of the acrylate-butadiene block polymer is 1-1.25, preferably 1-1.2; Preferably, based on the total weight of the acrylate-butadiene block polymer, the weight content of the metal element in the polymer is 200 ppm or less, preferably 100 ppm or less.
4. The acrylate-butadiene block polymer according to any one of claims 1 to 3, wherein The linear thermal expansion coefficient of the acrylate-butadiene block polymer after curing is 40×10 -6 m / m / ℃-80×10 -6 m / m / ℃, preferably 40×10 -6 m / m / ℃-70×10 -6 m / m / ℃, more preferably 40×10 -6 m / m / ℃-60×10 -6 m / m / ℃; Preferably, the peel strength between the coating formed by the acrylate-butadiene block polymer and the metal substrate is 1-1.3 N / mm, preferably 1.05-1.3 N / mm, and more preferably 1.1-1.3 N / mm; Preferably, after curing, the coating formed by the acrylate-butadiene block polymer has an interlayer bonding force of the metal substrate of 0.9-1.2 N / mm, preferably 0.95-1.2 N / mm, and more preferably 1-1.2 N / mm; Preferably, after the acrylate-butadiene block polymer is cured, the dielectric loss of the 10 GHz flat plate capacitor of the metal matrix laminate is ≤0.0042, preferably ≤0.0040, and more preferably ≤0.0038.
5. A method for preparing an acrylate-butadiene block polymer, characterized in that: The method comprises: (1) in the presence of a solvent, a structure regulator and an initiator, continuously adding 1,3-butadiene monomer into a reactor to carry out anionic solution polymerization reaction to obtain a polymerization reaction solution containing a butadiene polymer, wherein the contact is carried out at a temperature of 60-100° C., the structure regulator comprises component A and component B, the component A is a tertiary amine, the component B is an alkali metal alcohol salt, the molar ratio of the component B to the component A is 0.1-0.5:1, and the solvent is a solvent containing an aliphatic heterocyclic ring; (2) After the product obtained in step (1) is first contacted with an alkyl metal compound, diphenylethylene is added, and after a second contact, an acrylate monomer is added for copolymerization to obtain an acrylate-butadiene block polymer; wherein the amount of the acrylate monomer added is 3-10% by weight based on the total weight of the 1,3-butadiene monomer and the acrylate monomer.
6. The method according to claim 5, wherein: Based on the total weight of the 1,3-butadiene monomer and the acrylate monomer, the amount of the acrylate monomer added is 4-9 weight %; Preferably, the copolymerization reaction conditions include: polymerization temperature of -20°C to 20°C, polymerization time of 30-60min; Preferably, the acrylic acid ester monomer is at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate and methyl-2-hydroxyethyl (meth)acrylate.
7. The method according to claim 5 or 6, wherein: Based on 100 g of solvent, the rate of adding 1,3-butadiene into the reactor is 0.1-0.5 g / min, preferably 0.15-0.35 g / min; Preferably, the 1,3-butadiene monomer is continuously produced at a temperature of 60°C to 90°C.
8. The method according to any one of claims 5 to 7, wherein: In step (2), the alkyl metal compound is selected from an alkyl aluminum compound and / or an alkyl magnesium compound; Preferably, the alkyl metal compound is at least one selected from trimethylaluminum, triethylaluminum, tripropylaluminum, triisopropylaluminum, tributylaluminum, triisobutylaluminum, diethylmagnesium, dibutylaluminum and n-butyl-sec-butylmagnesium; Preferably, the molar ratio of the alkyl metal compound to the initiator is 0.5-3:1, preferably 1-2:1; Preferably, the first contact time between the product obtained in step (1) and the alkyl metal compound is 1-10 min, preferably 2-8 min.
9. The method according to any one of claims 5 to 8, wherein: The second contact time is 10-20 minutes; Preferably, the diphenylethylene is selected from 1,1-diphenylethylene and / or 1,2-diphenylethylene, preferably 1,1-diphenylethylene; Preferably, the molar ratio of the diphenylethylene to the initiator is 1-2:
1.
10. The method according to any one of claims 5 to 9, wherein: The component A is one or more compounds selected from the group consisting of: In formula I, R2 and R3 are the same or different and are independently C1-C6 alkyl groups, and R1 is a monovalent group shown in formula II, In formula II, m is an integer of 1-5, R4 and R5 are the same or different, and are independently a hydrogen atom or a C1-C6 alkyl group, R6 is -NR7R8 or a C3-C6 oxacycloalkyl group, R7 and R8 are the same or different, and are independently a C1-C6 alkyl group, Preferably, the component A is N,N,N',N'-tetramethylethylenediamine and / or N,N-dimethyl-tetrahydrofurfurylamine.
11. The method according to any one of claims 5 to 10, wherein: The component B is one or more compounds selected from the group consisting of: R9-O-M1 (Formula III) In formula III, R9 is C1-C 20 Alkyl, C1-C 20 Alkyl, or C6-C 30 The aromatic group, M1 is an alkali metal atom; Preferably, the heteroatom-containing substituent is a heteroatom-containing cycloalkyl group, and the heteroatom is preferably an oxygen atom, a sulfur atom or a nitrogen atom, more preferably an oxygen atom; Preferably, the component B is one or more of sodium tetrahydrofurfuryl alcohol, sodium tert-pentyl alcohol, sodium tert-butyl alcohol, sodium n-hexanolate and sodium menthol.
12. The method according to any one of claims 5 to 11, wherein: The molar ratio of the component B to the component A is 0.15-0.45:1, preferably 0.2-0.4:1; Preferably, the amount of component B used is 0.1-0.5 mol, preferably 0.2-0.4 mol, relative to 1 mol of the initiator.
13. The method according to any one of claims 5 to 12, wherein: The initiator is used in an amount such that the number average molecular weight of the prepared acrylate-butadiene block polymer is 3500-10000 g / mol, preferably 4500-8000 g / mol; Preferably, the initiator is an organic lithium initiator, preferably one or more selected from the compounds shown in formula IV, R 10 Li (Formula IV) In Formula IV, R 10 C1-C6 alkyl, C3-C 12 Cycloalkyl, C7-C 14 Arylalkyl or C6-C 12 The aromatic group; More preferably, the anionic polymerization initiator is n-butyl lithium and / or sec-butyl lithium; Preferably, the solvent is an oxacycloalkane, preferably tetrahydrofuran.
14. An acrylate-butadiene block polymer prepared by the method of any one of claims 5 to 13.
15. A composition comprising an acrylate-butadiene block polymer and at least one additive, wherein the acrylate-butadiene block polymer is the acrylate-butadiene block polymer according to any one of claims 1 to 4 and 14.
16. The composition according to claim 15, wherein The additive contains an antioxidant.
17. A polymer coating comprising the acrylate-butadiene block polymer of any one of claims 1 to 4 and 14, or the composition of claim 15 or 16.
18. Use of the acrylate-butadiene block polymer according to any one of claims 1 to 4 and 14, or the composition according to any one of claims 15 or 16 as a crosslinking agent, an adhesive or an electrical insulating material.